FEASIBILITY OF E-LEARNING PROJECTS AND ESTIMATION OF INFORMATION INFRASTRUCTURE NEEDS - Ali Abdulhussein Khaleel Alfadhel (Web of Journals Publishing, 2024)
This study focused on providing a vision of e-learning projects and their economic feasibility, especially in the Iraqi environment, and counting the gains achieved and the level of availability of infrastructure and supporting information, the study has found all the results extracted from the feasibility are good, the ability of the project to pay its short-term obligations was about (47%) of what is required, for the liquidity of the project it is by (26%), the project's ability to exploit the available resources was about (273%) of what is required, The project management was characterized by high efficiency in the use of working capital, where it is estimated at (283%) of what is required, the standard of using revenues to cover operational costs reached a good result estimated at (116%) approximately what is required, the profitability of the project to the total investments amounted to (46%) approximately, including annual inflation rates, the project is insensitive to the increase in costs and low revenues, and the most important recommendations were to submit suggestions to investment commissions and ministries that include some of their services Technical Committees and which are in line with the directions of the Iraqi e-government, Simplifying procedures and services to serve the citizen and provide greater information investment opportunities.
Keywords: Financial Feasibility, E-learning, Information infrastructure.